Occurrence OF Pectobacterium carotovorum strains isolated from potato soft rot in Morocco - Terta, M.; El Karkouri, A.; Ait M'hand, R.; Achbani, E.; Barakate, M.; Amdan, M.; Annajar, B.; El hassouni, M.; Val, F.; Bouteau, F.; Ennaji, M. M. (Cellular and Molecular Biology, 2010)
Pectobacterium carotovorum subsp. carotovorum, Pectobacterium astrosepticum and Pectobacterium chrysanthemi are the soft rot tuber of potatoes pathogens (Solanum tuberosum). The aim of this study was to determine the occurrence of these pathogens in Moroccan regions producing potatoes. Fifty three isolates of Pectobacterium were isolated on medium Crystal Violet Pectate. The comparison of their bacteriological characteristics with standard strains allowed us to conclude that all the isolates belonged to the Pectobacterium. With regard to phenotype characteristics, the variability that was found included 32 typical Pectobacetrium carotovorum subsp. carotovorum, 3 typical Pectobacterium atrosepticum, and 18 atypical Pectobacterium carotovorum subsp. carotovorum. Three strains of the atypical group; showed that the biochemical properties overlap among the Pectobacterium carotovorum and Pectobacterium chrysanthemi. These data were needed molecular characterization. However, the PCR amplification of total genomic DNA of 53 isolates with the two primers Y1/Y2 and P143/P145 yielded an amplified fragment of the expected size (434 bp) only with Y1/Y2, indicated that all the isolates collected and tested belonged to the Pectobacterium carotovorum species. On the basis the pathogenicity tests, these strains revealed that they were pectinolytic, and showed differences in aggressiveness against potato and leaves of tobacco.